ANALISIS HAK DAN KEWAJIBAN SUAMI-ISTRI DALAM BINGKAI KAJIAN KOMPARATIF HUKUM PERKAWINAN INTERNASIONAL - Nurul, Ilmiani; Ramadhani, Lintang (University of Islam Malang, 2024)
The sakinah and eternity of marriage shows that there is an aspect of humanism in marriage. This means that humanitarian principles must be the spirit in the formation and survival of a household. Regarding the rights and obligations of husband and wife, it is regulated in CHAPTER VI Article 30 to Article 34 of Law Number 1 of 1974 concerning Marriage. This research aims to compare and determine the balance between the rights and obligations of husband and wife in the view of Islamic law and positive law that applies in Asian countries, which are an Indonesia and Malaysia, and Middle Eastern countries, which are in Egypt. This research uses the qualitative research methods which is the library research as the data source. The data collection technique is to collect official data and from relevant literature. The research results and conclusions show that the marriage laws in Indonesia (Law and KHI) and Malaysia in the Sarawak State Islamic Family Law 2001 are the same. Both of them refer to the rules of Islamic law from four schools of thought. However, there are several points that are different. Meanwhile, codification of Family Law in Egypt is a form of development of traditional or classical Islamic family law.